Negotiating public space for livelihoods: about risks, uncertainty and power in the urban poor’s everyday life - Hackenbroch, Kirsten (ERDKUNDE, 2013)
Many urban poor depend on access to public space for everyday life. With this necessity to utilise public space comes the risks of being dislocated from a specific place and thus uncertainty about whether the current livelihood strategy can be maintained. The notion of risk here refers to the question of access rights, and thus to ‘social space’, which is produced through the various organisations and actors claiming space as well as the existence of social norms and values. This paper discusses the changing geographies of risk and uncertainty with regard to the negotiations of access to public space for urban livelihoods in an environment where informal institutions dominate. A partly ethnographic account of everyday life in a market place in a low-income settlement of Dhaka, Bangladesh, underlines the difficulty of securing one’s ‘right to space’. It furthermore shows how one’s position in social space and one’s access to sources of power can be utilised for minimising risk and uncertainty concerning access to urban public space.